Sosialisai pencegahan penyebaran covid 19 dengan gerakan masyarakat hidup sehat di kota padangsidimpuan - Siregar, Hotma Royani; Simamora, Asnil Adli (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2020)
COVID-19 (coronavirus disease 2019) is a disease caused by a new type of coronavirus, namely Sars-CoV-2, which was first reported in Wuhan China on December 31, 2019. Coronavirus is a collection of viruses that can infect the respiratory system. In most cases, this virus causes only minor respiratory infections, such as the flu. However, this virus can also cause severe respiratory infections, such as lung infections (pneumonia). This virus is transmitted through sputum droplets from the respiratory tract, for example when in a crowded closed room with poor air circulation or direct contact with droplets. So based on the above problems, we intend to carry out community service in the form of socialization of the prevention of Covid-19 transmission with the Healthy Living Community Movement in Padangsidimpuan City. The purpose of this activity is so that the community can prevent Covid-19 transmission by carrying out a healthy lifestyle. The public was very enthusiastic about receiving information related to the prevention of Covid-19 transmission through the giving and explanation of the leaflets that were distributed. COVID-19 (coronavirus disease 2019) is a disease caused by a new type of coronavirus, namely Sars-CoV-2, which was first reported in Wuhan China on December 31, 2019. Coronavirus is a collection of viruses that can infect the respiratory system. In most cases, this virus causes only minor respiratory infections, such as the flu. However, this virus can also cause severe respiratory infections, such as lung infections (pneumonia). This virus is transmitted through sputum droplets from the respiratory tract, for example when in a crowded closed room with poor air circulation or direct contact with droplets. So based on the above problems, we intend to carry out community service in the form of socialization of the prevention of Covid-19 transmission with the Healthy Living Community Movement in Padangsidimpuan City. The purpose of this activity is so that the community can prevent Covid-19 transmission by carrying out a healthy lifestyle. The public was very enthusiastic about receiving information related to the prevention of Covid-19 transmission through the giving and explanation of the leaflets that were distributed.